Pengaruh Preferensi Penggunaan Tangan Terhadap Kemampuan Visuospasial di Provinsi Lampung - Winati Nurhayu; Bobby Permana Putra; Gres Maretta; Jeane Siswitasari Mulyana; Andy Darmawan (Jurnal Penelitian Pendidikan IPA, 2023)
The preference for using the right or left hand for different uni-manual tasks is known as handedness. Handedness as functional asymmetry has a correlation with the asymmetric brain. Most types of tools have been developed for right-handed use, leading to different adaptations between left-handed and right-handed individuals. Visuospatial, as one of the cognitive processes, is the ability to visualize two- and or three-dimensional objects. This function allows individuals to remember, plan for the future, navigate, and make decisions, thus visuospatial is one of the primary mental aspects in humans. The aim of this study was to assess whether being left-handed was associated with visuospatial ability. Respondents in this study were 148 adult individuals who lived in Lampung Province. Handedness was assessed based on a questionnaire of self-confessed and hand preference of 10 daily activities. Hand grip performance was measured by using a hand dynamometer. The ability of visuospatial was assessed by using the Right-Left Discrimination method. The results of the visuospatial ability test showed that left-handed individuals had a better average score of visuospatial than right-handed ones (44.00 > 40.86). Males had better visuospatial ability than females (estimate = -0.0768; p-value: 0.0481). The influence of handedness on visuospatial ability was discussed